PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN DEEPFAKE PORNOGRAPHY DI INDONESIA: Legal Protection for Female Victims of Deepfake Pornography in Indonesia - Nareshya Aridia Putri; Wahyuni Retnowulandari (Reformasi Hukum Trisakti, 2026)
The development of artificial intelligence technology has given rise to new forms of digital-based sexual crimes, such as deepfake pornography, which threaten women’s right to privacy and dignity. This phenomenon legal problem issues concerning the effectiveness of legal protection for women as victims. This study examines legal protection for women victims of deepfake pornography in Indonesia based on the Law on Information and Electronic Transactions, Law Number 44 of 2008 on Pornography, and the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). The result and conclusion research employs a descriptive-analytical normative legal research method, supported by library research. The findings indicate that legal protection remains suboptimal due to fragmented regulations, challenges in digital evidence, and limited legal responses to technological developments, thereby necessitating the strengthening of regulations and victim-centered law enforcement